Darcy-Forchheimer flow of Cu/TiO2 nanoliquid past a stretching sheet with heat generation/consumption. Issue 1 (1st November 2022) - Divya, S; Eswaramoorthi, S; Loganathan, K
Abstract: The present study explores the Darcy-Forchheimer flow of a water-based Cu/TiO2 nanoliquid with heat generation/consumption. The appropriate transformations are used to transform the coupled non-linear PDEs into ODEs and these equations are solved numerically by MATLAB bvp4c procedure. The effect of various physical parameters on velocity, temperature, skin friction coefficient and local Nusselt number are reported in tabular and graphical format. The velocity of both directions decreases for the larger quantity of porosity and suction/injection parameters. The temperature of the fluid increases when strengthening the heat production/consumption parameter and it reduces by varying the values of the Prandtl number. The surface shear stress increases when rising the Darcy-Forchheimer number. The local Nusselt number diminishes when escalating the suction/injection parameter.